FEMINISME POSMODERN LUCE IRIGARAY: PEMBEBASAN PEREMPUAN DARI BAHASA PATRIARKI - Pratiwi, Ni Putu Sri; Nugroho, Wahyu Budi; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
ABSTRACT This journal aims to explain the insights of postmodern feminism by Luce Irigaray in the framework of sociological study and analyzing the contextualization of women's liberation from patriarchal language according to postmodern feminism. The postmodern feminism of Luce Irigaray criticizes the view of falogocentrism which is only based on the point of view of men in the language system and prevent women who represent women's femininity. Irigaray declared that if women wanted to make herself more than asking for "waste" in the world of men, there are three action could be taken by women. First, women can avoid gender neutral languages. ??Second, women can make women's language. Third, in an effort to be herself, women can ask for imitations that men need for women. Keywords: Postmodern feminism, Luce Irigaray, women liberation, patriarchal language